An Analytical Solution for Acoustic Emission Source Location for Known P Wave Velocity System. (27th March 2014) - Dong, Longjun; Li, Xibing; Xie, Gongnan
Abstract : This paper presents a three-dimensional analytical solution for acoustic emission source location using time difference of arrival (TDOA) measurements from N receivers, N ⩾ 5 . The nonlinear location equations for TDOA are simplified to linear equations, and the direct analytical solution is obtained by solving the linear equations. There are not calculations of square roots in solution equations. The method solved the problems of the existence and multiplicity of solutions induced by the calculations of square roots in existed close-form methods. Simulations are included to study the algorithms' performance and compare with the existing technique.